Global Energy Supply and Emissions - Gethmann, Carl Friedrich. author. aut Link
XXVI, 322 p. 158 illus., 137 illus. in color.
Keywords: This book offers an authoritative analysis of the state-of-the art in energy and climate research and policy. It starts by describing the current status of technologies that are expected to have an influence on the energy systems of the future. For an adequate evaluation, it presents the latest findings on the effects of energy supply and consumption as well as of the emissions on both the environment and people’s health. This is followed by an extensive discussion of the economic and social problems related to climate change, the need for energy transitions, and other issues that may require public investment and international agreements. The book reviews the problem of energy policy from a global perspective, providing readers with the technical, political, economic and ethical background needed to understand the current situation and work at better solutions for a sustainable, just and prospering world.